(3dG hUa deG CfG ajg(B: s (3TYQ YQHj eYGUQ(B/ s - AlGhanem, Nujoom (3GdZGfe, fLhes ((3HjQhJ; CQOf;s (3GdeDSSI GdYQHjI ddOQGSGJ h GdfTQ;s, 2005)
Selection of work.
Title translation: There is no description of what I am in- Nujoom AlGhanem
Arabic
Keywords: PN1010-1525 Poetry; UAE